2012
DOI: 10.1515/ijnsns-2011-097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging Treatment on Dynamic Behavior of Mg-Gd-Y Alloy

Abstract: Magnesium alloy is very attractive in many industrial applications due to its low density. The structure-property relationships of the magnesium alloy under quasi-static loading have been extensively investigated. However, the dynamic behavior, particularly the mechanism of high-rate plastic deformation, of the magnesium alloy requires more in-depth investigations. In this paper, the effect of aging treatment on the quasi-static and dynamic properties of a typical rare earth Mg-Gd-Y magnesium alloy is investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
3
0
0
Order By: Relevance
“…e and f) show that mainly round‐shaped particles containing more Zr appeared in the T6 state. Similar observations were also reported by Wang et al . Based on the Mg–Gd phase diagram and Mg–Y phase diagram, only one single phase solid solution would be expected in the Mg‐10Gd‐3Y‐0.5Zr (GW103K) alloy during solution treatment at 500 °C.…”
Section: Microstructures Of Re–mg Alloyssupporting
confidence: 89%
See 2 more Smart Citations
“…e and f) show that mainly round‐shaped particles containing more Zr appeared in the T6 state. Similar observations were also reported by Wang et al . Based on the Mg–Gd phase diagram and Mg–Y phase diagram, only one single phase solid solution would be expected in the Mg‐10Gd‐3Y‐0.5Zr (GW103K) alloy during solution treatment at 500 °C.…”
Section: Microstructures Of Re–mg Alloyssupporting
confidence: 89%
“…3e and f) show that mainly round-shaped particles containing more Zr appeared in the T6 state. Similar observations were also reported by Wang et al 76 Based on the Mg-Gd phase diagram 51 and Mg-Y phase diagram, 79 only one single phase solid solution would be expected in the Mg-10Gd-3Y-0.5Zr (GW103K) alloy during solution treatment at 500°C. It was reported that the solubility of Gd and Y in Mg at 500°C was about 20wt% and 10wt%, respectively, 51 whereas the solubility of Zr in Mg was very limited.…”
Section: Heat-treated Re-mg Alloyssupporting
confidence: 89%
See 1 more Smart Citation